Comparison of Simulation and Experimental Axial Loadings for Hydromechanical Bulge Forming of Copper Cross-Joints - Jacek Chalupczak; Tomasz Milek (Communications - Scientific letters of the University of Zilina, 2005)
Hydromechanical bulging is applied mainly to the series production of hydraulic installation and sanitary facilities including tubes with a changeable diameter, T-pipes and cross-joints. The process consists in placing a tube segment in a die-cavity, pouring some liquid over it and sealing the faces. As a result the liquid pressure rises and the pipe is upset. The basic parameters of the hydromechanical process of bulge forming are: liquid pressure and axial loading. The simulations of hydromechanical bulge forming were performed using MSC Marc software based on the finite element method. The calculation results were compared with the experimental data especially to study axial loading for different ratios d/D, so/D and for different variations of internal pressure. The results of numerical simulations of axial loading are in good agreement with the experimental data for established = 0,15.